Operations et transactions sur DTS : Premiere periode de base. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1973)
.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet